ANALISIS PERBANDINGAN KEPATUHAN KUNJUNGAN PASIEN HIPERTENSI TAHUN 2023 DAN 2024 DI PUSKESMAS PUNDONG BANTUL - Supatmi; Pamungkasih, Wahyu; Pamungkasih, Eni; Novita Kumalasari, Dian (Jurnal Riset Daerah, 2024)
Patient adherence to hypertension follow-up visits at Pundong Community Health Center is a primary concern in hypertension management. This study aims to analyze the comparison of patient adherence between 2023 and 2024 and identify factors influencing patient adherence. This research utilized a cross-sectional design with a quantitative approach. Data were collected from hypertension patient visit documentation at Pundong Community Health Center from January 2023 to August 2024. The sample was taken using purposive sampling, involving patients who had been diagnosed with hypertension. Variables analyzed included visit frequency and patient age. The results showed a decrease in the number of patients attending visits from 2023 to 2024, although patient adherence increased during this period. This study found no significant relationship between older age and adherence levels, despite many studies showing that older patients tend to have higher adherence, possibly due to increased health awareness. Factors such as knowledge about hypertension, family support, and access to healthcare facilities played significant roles in determining adherence. Key challenges identified include a lack of knowledge, difficulty in accessing care, and dissatisfaction with healthcare services. Despite the decrease in the number of visits from 2023 to 2024, patient adherence to hypertension treatment showed improvement, indicating the effectiveness of possible interventions. Older patients demonstrated better adherence, while issues such as lack of knowledge and difficulty accessing care still need to be addressed. Improving patient education, enhancing family support, and refining healthcare systems are essential steps to further enhance adherence and the overall management of hypertension.